2006
DOI: 10.1111/j.1365-313x.2006.02697.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and divergence of plant microRNA genes

Abstract: MicroRNA (miRNA) is one class of newly identified, small, non-coding RNAs that play versatile and important roles in post-transcriptional gene regulation. All miRNAs have similar secondary hairpin structures; many of these are evolutionarily conserved. This suggests a powerful approach to predict the existence of new miRNA orthologs or homologs in other species. We developed a comprehensive strategy to identify new miRNA homologs by mining the repository of available ESTs. A total of 481 miRNAs, belonging to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
583
8
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 669 publications
(662 citation statements)
references
References 57 publications
61
583
8
10
Order By: Relevance
“…Several families of microRNAs (miRNAs) have been found in green plants ranging from algae, mosses, ferns, gymnosperms and angiosperms (Floyd and Bowman, 2004;Arazi et al, 2005;Axtell and Bartel, 2005;MolnĂĄr et al, 2007;Zhang et al, 2006;Zhao et al, 2007) suggesting that the regulation by miRNA is ancient in origin. At least 88 annotated miRNA families have been identified in the moss P. patens and 44 in the lycopod Selaginella moellendorffii (Axtell et al, 2007;Fattash et al, 2007).…”
Section: Bryophytes As An Ancient Lineage May Have Retained Many Novementioning
confidence: 99%
“…Several families of microRNAs (miRNAs) have been found in green plants ranging from algae, mosses, ferns, gymnosperms and angiosperms (Floyd and Bowman, 2004;Arazi et al, 2005;Axtell and Bartel, 2005;MolnĂĄr et al, 2007;Zhang et al, 2006;Zhao et al, 2007) suggesting that the regulation by miRNA is ancient in origin. At least 88 annotated miRNA families have been identified in the moss P. patens and 44 in the lycopod Selaginella moellendorffii (Axtell et al, 2007;Fattash et al, 2007).…”
Section: Bryophytes As An Ancient Lineage May Have Retained Many Novementioning
confidence: 99%
“…Similar observation was also reported in plant genomes. Recent work by Zhang et al [38] has shown, from more than 6 million plant EST sequences, a total of 481 miRNAs that belong to 37 miRNA families from 71 different plant species. Plant miRNAs have been demonstrated to be conserved across gymnosperms, fern, moss, and liverwort [3].…”
Section: The Mirna Gene Familiesmentioning
confidence: 99%
“…The phylogenetic distribution and evolution of animal and plant miRNAs have been studied in recent reports [2][3][4][5][6][7][8][9][10][11][12]. In animals, the expansion of miRNAs is an ongoing process [5].…”
Section: Introductionmentioning
confidence: 99%